Frictional behavior of talc‐calcite mixtures. Issue 9 (26th September 2015) - Giorgetti, C.; Carpenter, B. M.; Collettini, C.
Abstract Faults involving phyllosilicates appear weak when compared to the laboratory‐derived strength of most crustal rocks. Among phyllosilicates, talc, with very low friction, is one of the weakest minerals involved in various tectonic settings. As the presence of talc has been recently documented in carbonate faults, we performed laboratory friction experiments to better constrain how various amounts of talc could alter these fault's frictional properties. We used a biaxial apparatus to systematically shear different mixtures of talc and calcite as powdered gouge at room temperature, normal stresses up to 50 MPa and under different pore fluid saturated conditions, i.e., CaCO3‐equilibrated water and silicone oil. We performed slide‐hold‐slide tests, 1–3000 s, to measure the amount of frictional healing and velocity‐stepping tests, 0.1–1000 µm/s, to evaluate frictional stability. We then analyzed microstructures developed during our experiments. Our results show that with the addition of 20% talc the calcite gouge undergoes a 70% reduction in steady state frictional strength, a complete reduction of frictional healing and a transition from velocity‐weakening to velocity‐strengthening behavior. Microstructural analysis shows that with increasing talc content, deformation mechanisms evolve from distributed cataclastic flow of the granular calcite to localized sliding along talc‐rich shear planes, resulting in a fully interconnected network of talc lamellae from 20% talc onward. Our observations indicate that in faults where talc and calcite are present, a low concentration of talc is enough to strongly modify the gouge's frictional properties and specifically to weaken the fault, reduce its ability to sustain future stress drops, and stabilize slip.